'Talent' mentalities : young people's experience of being in a sports talent development programme - Turner, G. (Liverpool John Moores University, 2016)
Article 12 of The UN Convention on the Rights of the Child grants each young person the right to express their view, have their opinion considered and have their say in decisions that affect them. Previous research on talent development in sport has however failed to recognise the voice of the young person or regard the participant as an autonomous agent. This study employed phenomenological enquiry to focus on the conditions of lived reality to afford the young person the opportunity to convey their unique experience. The aim of the research was to employ a participatory approach to explore the essence of young people's conscious experience of Talent Development Programmes in sport. My co-collaborators were eight young people aged between 13 and 17, (two females: netball and gymnastics, and six males: rugby 3, discus, angling, and badminton), who all attended the same school and were all members of a Sports National Governing Body Talent Development Programme. Over twelve months each participant utilised their individual preference to communicate depictions of self, drawing upon interview, conversation, Twitter, video, photo and observation of training and performance. Results were presented in the form of individual vignettes generated from researcher and participant interaction and constructed according to hermeneutical interpretation. Young people`s stories reveal the essence of talent development through the experience of uncertainty and endeavour; talent development experience teaches young people to self-present in response to perceived injustice; and individual progress is characterised by self-regulation and the pursuit of personal empowerment. The research demonstrates that when young people are involved in active decision making about their learning and their lives they feel better respected and understood. Academics and practitioners must now accept a responsibility to engage with the unique lived experience of the young person`s reality to find better ways to listen to the young person`s voice to support their talent development experience in sport.